Differentiation of viral and bacterial infections in children: Potential of myxovirus resistance protein A - Piri, Ruut (fi=Turun yliopisto|en=University of Turku|, 2025)
Differentiating between viral and bacterial infections in children is a diagnostic challenge, often leading to antibiotic overuse and driving antimicrobial resistance. Current diagnostic methods have notable limitations, highlighting the need for novel tools. Blood myxovirus resistance protein A (MxA) is a promising biomarker for viral infections, given its broad antiviral activity and rapid induction during viral illness. Host gene expression analysis further expands diagnostic possibilities by identifying biosignatures unique to viral or bacterial infections. This thesis comprises four studies. Study I assessed respiratory viruses and antiviral MxA responses in children with febrile urinary tract infections (UTIs). Study II evaluated MxA as a biomarker for viral infection in children hospitalised with a suspected serious infection. Study III investigated the accuracy of a novel point-of-care (POC) MxA test and its ability to differentiate viral from bacterial infections in febrile children at the emergency department. Study IV explored host gene expression signatures to distinguish bacterial from viral infections. In this study, respiratory viruses were frequently detected in children with febrile UTIs and other serious bacterial infections. Blood MxA levels were significantly higher in viral infections and viral-bacterial coinfections compared to bacterial infections. In children with a suspected serious infection, a blood MxA cutoff of 256 μg/L differentiated viral from bacterial infections with a sensitivity of 74% and specificity of 80%. The novel POC MxA test provided rapid results with acceptable accuracy compared to the reference method, supporting its use in acute care settings. A POC MxA level of 101 μg/L differentiated between viral and bacterial infections with 92% sensitivity and 91% specificity. A 2-transcript host gene expression signature (TSPO and SECISBP2) distinguished bacterial and viral-bacterial coinfections from viral infections with 77% sensitivity and 87% specificity. This thesis highlights MxA and host gene expression analysis as promising advancements in paediatric infectious disease diagnostics. The high prevalence of viral-bacterial coinfections challenges novel diagnostic approaches and supports the use of MxA in combination with bacterial biomarkers.

Lasten virus- ja bakteeri-infektioiden erotusdiagnostiikka: veren myksovirusresistenssiproteiini A:n potentiaali Lasten virus- ja bakteeri-infektioiden erotusdiagnostiikkaan tarvitaan uusia mene-telmiä, sillä nykyinen diagnostinen epävarmuus johtaa antibioottien liikakäyttöön ja pahentaa antibioottiresistenssiä. Myksovirusresistenssiproteiini A (MxA) on lupaava virusinfektion merkkiaine, sillä sen pitoisuus veressä suurenee nopeasti useimpien virusinfektioiden yhteydessä. Veren geeniekspressioanalyysin avulla voidaan määrittää virus- ja bakteeri-infektioille ominaisia muutoksia geenien ilmentymi-sessä. Väitöskirja koostuu neljästä tutkimuksesta. Ensimmäisessä osatyössä tutkimme hengitystievirusten esiintymistä ja antiviraalista MxA-vastetta kuumeista virtsatie-infektiota sairastavilla lapsilla. Toisessa osatyössä arvioimme MxA:n suorituskykyä virusinfektion merkkiaineena sairaalahoitoon vakavan bakteeri-infektion epäilyn vuoksi otetuilla lapsilla. Kolmannessa osatyössä vertasimme uuden MxA-pikatestin mittaustarkkuutta laboratoriomenetelmään verrattuna. Arvioimme myös MxA:n kykyä erottaa kuumeisten lasten virus- ja bakteeri-infektiot toisistaan päivystyspoli-klinikalla. Neljännessä osatyössä tutkimme geeniekspressioanalyysin potentiaalia virus- ja bakteeri-infektioiden erotusdiagnostiikassa. Tutkimuksessa kuumeiseen virtsatieinfektioon ja muihin bakteeri-infektioihin sairastuneilta lapsilta löydettiin usein hengitystieviruksia. Veren MxA-pitoisuus oli selvästi suurempi virusinfektiota tai viruksen ja bakteerin sekainfektiota sairastavilla lapsilla verrattuna yksinomaan bakteeritautia sairastaviin. Sairaalahoitoisilla poti-lailla MxA:n raja-arvo 256 μg/l erotteli virusinfektiot bakteeritaudeista 74 %:n herkkyydellä ja 80 %:n tarkkuudella. MxA-pikatestin todettiin soveltuvan päivystys-käyttöön, sillä sen suorittaminen oli nopeaa ja mittaustarkkuus riittävä. Pikatestin raja-arvolla 101 μg/l eroteltiin virus- ja bakteeri-infektiot 92 %:n herkkyydellä ja 91 %:n tarkkuudella. Geeniekspressioanalyysissä kahden eri tavoin ilmentyvän geenin yhdistelmä (TSPO ja SECISBP2) erotti bakteeri- ja sekainfektiot virustaudeista 77 %:n herkkyydellä ja 87 %:n tarkkuudella. MxA-määritys ja geeniekspressioanalyysi ovat lupaavia menetelmiä lasten infektiosairauksien diagnostiikassa. Sekainfektioiden yleisyyden vuoksi MxA-määritys kannattaa yhdistää bakteeri-infektion merkkiaineen määritykseen.